Perbedaan Pengaruh Latihan Plyometrik terhadap Kecepatan Tendangan T Pencak Silat Tapak Siaga - Nur Aminah Hidayanti; Bagus Kuncoro; Risa Agus Teguh Wibowo (Departement of Mathematics Education, 2024)
The aim of the research is to determine the difference in the effect of plyometrics split jumps and double leg speed hop training on T kick speed among Pencak Silat students at Tapak Siaga Rayon Banyuanyar. Based on the results of the data analysis, the conclusions obtained are: (1) There is a significant difference in influence between the Plyometrics split jumps method and the double leg speed hop on the speed of T kicks in Pencaksilat among Pencak Silat students at Tapak Siaga Rayon Banyuanyar in 2023. This is proven by the results of the final test calculations for each group, namely tcount = 3.160 which is smaller than ttable = 2.145 with a significance level of 5%. (2) Plyometrics split jumps training has a better effect than the double leg speed hop method on the speed of T kicks in Pencaksilat among Pencak Silat students Tapak Siaga Rayon Banyuanyar in 2023. Based on the percentage increase in T kick speed in pencaksilat, it shows that group 1 (the group that received treatment with the Plyometrics split jumps method) was 35.616% > group 2 (the group that received the Double leg speed hop) was 32.168%.